Effect of Hataedock Treatment on Epidermal Structure Maintenance through Intervention in the Endocannabinoid System. (22nd January 2020) - Kim, Hee-Yeon; Ahn, Sang-hyun; Yang, In-Jun; Park, Sun-Young; Kim, Kibong
Abstract : The aim of this study was to investigate the efficacy of Hataedock (HTD) on skin barrier maintenance through the endocannabinoid system (ECS) intervention in Dermatophagoides farinae -induced atopic dermatitis (AD) NC/Nga mice. Douchi (fermented Glycine max Merr.) extracts prepared for HTD were orally administered to NC/Nga mice at a 20 mg/kg dose. Then, Dermatophagoides farinae extract ( Df E) was applied to induce AD-like skin lesions during the 4th–6th and 8th–10th weeks. Changes in the epidermal structure of the mice were observed by histochemistry, immunohistochemistry, and TUNEL assay. The results showed that HTD significantly reduced the clinical scores (p < 0.01 ) and effectively alleviated the histological features. In the experimental groups, increased expression of cannabinoid receptor type (CB) 1, CB2, and G protein-coupled receptor 55 (GPR55) and distribution of filaggrin, involucrin, loricrin, and longevity assurance homolog 2 (Lass2) indicated that HTD maintained the epidermal barrier through intervening in the ECS. The expression of E-cadherin and glutathione peroxidase 4 (GPx4) was increased, and the levels of cluster of differentiation 1a (CD1A) were low. Moreover, the apoptosis of inflammatory cells was elevated. The production of phosphorylated extracellular signal-related kinase (p-ERK), phosphorylated c-Jun amino-terminal kinase (p-JNK), and phosphorylated mammalian target of rapamycin (p-mTOR) was low, and epidermal thickness was decreased. Besides, the expression levels of involucrin were measured by treating genistein, an active ingredient of Douchi extract, and palmitoylethanolamide (PEA), one of the ECS agonists. The results showed that genistein had a better lipid barrier formation effect than PEA. In conclusion, HTD alleviates the symptoms of AD by maintaining skin homeostasis, improving skin barrier formation, and downregulating inflammation, through ECS intervention.